Evaluation of coatings for Mg alloys for biomedical applications - Abidin, N.I.Z.; Da Forno, A.; Bestetti, M.; Martin, D.; Beer, A.; Atrens, A. (2015)
The aim of this work was to assess a number of coatings developed for Mg for biomedical applications. The Mg substrates were high-purity (HP) Mg and ME10, an alloy recently developed for improved extrudability. The research utilized the new fishing-line specimen configuration to allow direct comparison to our recent in vivo and in vitro measurements. The in vitro measurements were immersion tests of fishing-line specimens immersed in Nor's solution at 37 degrees C. Tests of substantial duration are needed because the corrosion rates of uncoated samples are low. Nor's solution is the designation given to Hank's solution through which CO2 is bubbled at a partial pressure of 0.009atm. In this solution, pH is maintained constant by the interaction of CO2 and the bicarbonate ions in the solution. This is the same buffer as that which maintains the pH of blood. Coatings examined were: (i) an anodization using a bio-friendly alkaline electrolyte consisting of phosphate, borate, and metasilicate, (ii) octyltrimethoxysilane (OSi), (iii) 1,2-bistriethoxysilylethane (BTSE), (iv) anodization+OSi, and (v) anodization + BTSE. The performance of coated samples was comparable to or better than that of the uncoated samples, and there was a substantially better performance for the ME10 samples after anodization+OSi. Reasons for the various performances are discussed.